Model analysis of worst place scenarios for nuclear accidents in the northern marine environment. (March 2016) - Kauker, F.; Kaminski, T.; Karcher, M.; Dowdall, M.; Brown, J.; Hosseini, A.; Strand, P.
Abstract: The North and Nordic Seas contains some of the world's most important fishery resources and is an area of significant traffic involving nuclear powered vessels and transports of nuclear and radioactive materials. Consumer awareness to even rumors of radioactive contamination imparts a special vulnerability to this region. The effective assignation of emergency resources, design of monitoring programs and provision of information regarding accidents relies upon an a-priori analysis of potential impacts. To this end, an adjoint sensitivity analysis regarding potential impacts on the most important regional fishery was conducted with a view towards development of a system capable of providing information regarding potential contaminant dispersal from any point within the North and Nordic Seas. Results indicate that the area is potentially vulnerable to releases of radioactive materials over a much wider area than has previously considered. Highlights: An adjoint sensitivity analysis of the northern marine area was conducted. Potential impacts on the most important regional fishery were assessed. The fishery is vulnerable to releases of contaminants over a much wider area than previously considered.